The high prevalence of inappropriate feeding among infants presenting with an apparent life-threatening event - Katsuaki Kojima; Katie Mckinley; Pamela Donohue; Yakov Sigal (The Turkish Journal of Pediatrics)
Although there are anecdotal reports of a link between inappropriate feeding and an apparent life-threatening event (ALTE), previous studies have not examined this association in a cohort of affected infants. This study compared the feeding behaviors of infants who have had an ALTE with age- and sex-matched controls. This is a single-center case control study. Forty-six term infants aged 6 months or less, who were hospitalized over a 34-month period following an ALTE, comprised the study sample; 92 age- and sex-matched controls were recruited from a wellness clinic. Feeding practices reported by parents were evaluated for their appropriateness with respect to the volume of each feeding, and the frequency and total volume of feedings per 24-hour period, based on the American Academy of Pediatrics guidelines. Comparisons were made between the ALTE cases and controls. Inappropriately fed infants were compared with the rest of the sample. The ALTE and control groups were similar with respect to the prevalence of breastfeeding, insurance, birth weight, and weight percentile at presentation. The ALTE group had a lower prevalence of appropriate feeding compared to the control group (43.5% versus 63.0%, p = 0.029). Overfed infants were at a higher weight percentile at the time of presentation (46.5th percentile versus 31.4 < sup > th < /sup > percentile, p = 0.037). These results represent the association between ALTE and inappropriate feeding practice, which emphasizes the need for assessment and education regarding feeding practices in patient presenting with an ALTE.